Advance-Purchase Financing of Projects with Few Buyers - Marco Sahm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
I investigate a simple model of advance-purchase contracts as a mode of financing costly projects. The analysis can easily be reinterpreted as a model of monopolistic provision of excludable public goods under private information. An entrepreneur has to meet some capital requirement in order to start production and sell the related good to a limited number of potential buyers who are privately informed about their willingness to pay. I find that advance-purchase arrangements allow to finance more costly projects than traditional funding sources. The entrepreneur is able to use advance-purchase surcharges as a price discrimination device. However, the discriminatory power is limited by the problem of free-riding which aggravates for an increasing number of potential buyers. I apply the model to research and development activities in the health industry discussing the availability of new drugs and vaccines in poor countries.
Keywords: D42; H41; L12; 330